Forced air cooled heat sink with uniformly distributed temperature of power electronic modules. (25th November 2021) - Bünnagel, Christian; Monir, Shafiul; Sharp, Andrew; Anuchin, Alecksey; Durieux, Olivier; Uria, Ikea; Vagapov, Yuriy
Highlights: Low-cost improvement of conventional heat sink for power electronic modules. Redistribution of the airflow through the heat sink fins using V-cut guide plate. Uniform distribution of the temperature across the power electronic modules. Modelling and verification of the proposed power semiconductor cooling system. Abstract: The paper discusses an approach to the design of the forced air-cooling heat sink for power electronic application to uniformly distribute the temperature of the semiconductor modules fixed on the top of the heat sink. The proposed approach suggests a minor modification of a conventional fin-based heat sink commonly manufactured for cooling of power electronic modules. Following the proposed modification, an air guide plate having a V-shaped cut is attached to the bottom of the heat sink to redistribute the airflow through the fins. To verify the proposed approach, the modified forced air-cooling system for a power electronic circuit comprising of three IGBT modules was modelled and numerically simulated using Ansys Fluent software under steady-state conditions. The numerical analysis was conducted for a range of power loss 50–100 W in each IGBT module and an airspeed of 5 m/s through the heat sink. The simulation results have shown a good uniform distribution of the temperature across the IGBT modules where the temperature difference does not exceed 0.21 °C.